Genre Structure Multistage in E. Zamyatin’s “We” (Proceedings of Southern Federal University. Philology, 2018)
Veronika P. Gredel (St. Petersburg, Russian Federation)E. Zamyatin’s “We” is interpreted as peculiar of author’s himself and imaginary co-author’s D-503. For author “We” is cosmos, for D-503 – numbers of One State. “We” represents a synthesis of genres formations, which can be identified as composition-sense steps of the novel: from author’s point of view – an anti-utopia novel and a classical tragedy; from narrator’s D-503 side – a synopsis, diary and drama.Key words: E. Zamyatin, genre, “WE”, modus, concept, epitaph, “the wisest of all lines”.DOI 10.23683/1995-0640-2018-4-179-187